Biomembrane-wrapped gene delivery nanoparticles for cancer therapy - Li, Jie; Zeng, Huamin; Li, Luwei; Song, Ming; Dong, Mingqing (Frontiers in Bioengineering and Biotechnology, 2023)
As a promising strategy, gene delivery for cancer treatment accepts encouraging progress due to the high efficacy, low toxicity and exclusive selectivity. However, the delivery efficiency, specific biological distribution, targeted uptake and biosafety of naked nucleic acid agents still face serious challenges, which limit further clinical application. To overcome the above bottleneck, safe and efficient functional nanovectorss are developed for improving the delivery efficiency of nucleic acid agents. In recent years, emerging membrane-wrapped biomimetic nanocapsules (MBNPs) based on the concept of “imitating nature” are well known for their advantages, such as low immunogenicity and long cycle time, and especially play a crucial role in improving the overall efficiency of gene delivery and reducing adverse reactions. Therefore, the combination of MBNPs and gene delivery is an effective strategy to enhance tumor treatment efficiency. This review presents the mechanism of gene therapy and the current obstacles to gene delivery. Particularly, the latest development of gene delivery MBNPs and the strategies to overcome these obstacles are summarized. Finally, the future challenges and prospects of gene delivery MBNPs toward clinical transformation are introduced. The principal purpose of this review is to discuss the biomedical potential of gene delivery MBNPs for cancer therapy, and to provide guidance for further enhancing the efficiency of tumor gene therapy.